Compact slot antenna with enhanced band‐edge selectivity and switchable band‐notched functions for UWB applications. Issue 7 (18th March 2019) - Yang, Hailong; Xi, Xiaoli; Zhao, Yuchen; Tan, Yumeng; Yuan, Yanning; Wang, Lili
Abstract : In this study, a new reconfigurable stepped slot antenna with enhanced band‐edge selectivity of the UWB passband and switchable band‐notched characteristic is presented. Good out‐of‐band rejection and sharp cut‐off at band‐edge are achieved by the use of defected ground structure (DGS) and a parasitic slot near the stepped slot. The well‐designed DGS not only produces transmission zero to obtain good cut‐off property in upper sideband but also provides better impedance matching of in‐band. The frequency range of the proposed antenna is from 3.1 to 11.1 GHz (114%) with the reflection coefficient < − 10 dB. The shape factor is 1.05, which indicates that the proposed design has an excellent selectivity. To obtain the notched band, two passive strip lines near the feeding line are designed. Furthermore, the reconfigurable function with four states can be easily realised by the control of two diodes between the passive strip line and the ground. The structures of the notched band and bias circuit are relatively simple and independent of antenna radiation structure. The performance of the antenna is presented and compared with other competitive antennas. The proposed design has many significant advantages in dimension, good out‐of‐band characteristics, and controllable states for different UWB applications.